2021
DOI: 10.1162/qss_a_00123
|View full text |Cite
|
Sign up to set email alerts
|

Towards automated analysis of research methods in library and information science

Abstract: Previous studies of research methods in LIS lack consensus in how to define or classify research methods, and there have been no studies on automated recognition of research methods in the scientific literature of this field. This work begins to fill these gaps by studying how the scope of ‘research methods’ in LIS has evolved, and the challenges in automatically identifying the usage of research methods in LIS literature. 2,599 research articles are collected from three LIS journals. Using a combination of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Several studies attempted to understand the research methods used by LIS researchers while designing their research study (Chu and Ke, 2017; Gauchi-Risso, 2016; Jamali, 2018; Kim and Jeong, 2006; Togia and Malliari, 2017; Ullah and Ameen, 2018; Zhang et al, 2021) and country-specific studies (Ferran-Ferrer et al, 2017; Lou et al, 2021). For instance Chue and Ke (2017) analyzed research methods of more than 1900 articles from LIS journals and attempted to explore the research methods and concluded that the research methods should be classified by the techniques used to collect data rather by the adopted data analysis technique.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies attempted to understand the research methods used by LIS researchers while designing their research study (Chu and Ke, 2017; Gauchi-Risso, 2016; Jamali, 2018; Kim and Jeong, 2006; Togia and Malliari, 2017; Ullah and Ameen, 2018; Zhang et al, 2021) and country-specific studies (Ferran-Ferrer et al, 2017; Lou et al, 2021). For instance Chue and Ke (2017) analyzed research methods of more than 1900 articles from LIS journals and attempted to explore the research methods and concluded that the research methods should be classified by the techniques used to collect data rather by the adopted data analysis technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Togia and Malliari (2017) analyzed the research approach, research methodology and method of data analysis applied in 440 research articles published in LIS journals and concluded that majority of articles applied empirical research were in the areas of “information retrieval,” “information behaviour,” “information literacy,” “library services,” and “organization and management.” Ullah and Ameen (2018) using quantitative systematic review to investigate the methods used by LIS researchers and concluded that survey is most common method and most of studies applied descriptive statistics to reach conclusions. In a recent study, Zhang et al (2021) attempted to automatically detect the research methods adopted in articles implementing a combination of content analysis and text mining techniques and concluded that a diverse range of methods are used by LIS researchers. Similarly, Ferran-Ferrer et al (2017) attempted to analyze the research methods adopted by the Spanish LIS researchers and Lou et al (2021) recently attempted the same for the Chinese LIS researchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This evolution of interdisciplinary research paradigms has led to the development of new research foci, organization of interdisciplinary conferences, establishment of international scientific societies, and creation of new journals, among others [1]. As the landscape of scientific disciplines continues to differentiate, classification systems are being developed to better reflect this dynamic reality and facilitate the study of knowledge production and dissemination, and as such can serve important classification functions [2][3][4][5]. Scientometric analysis and the classification of scientific literature provides an indispensable basis for the evaluation and synthesis of published literature and improves the efficiency of researchers' information search.…”
Section: Introductionmentioning
confidence: 99%
“…In their current form, these systems are too broad to adequately reflect the more complex, fine-grained cognitive reality; therefore, their scope is limited and they only indicate broad scientific domains or general disciplines. Empirical studies [5] as well as theoretical arguments by researchers [13] emphasize the need for fine-grained classification approaches. A recent study by Wahid et al [11] found that focused research communities can be distinguished based on publication associations, and publication practices and patterns may vary within these communities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to maintaining an informed view of methods, the method evolution can be used to analyze the progress of a discipline. According to the method trend in a discipline, researchers can infer the changes in the research tasks and then get the development of research topics (Zhang, Tam & Cox, 2021).…”
Section: Introductionmentioning
confidence: 99%